PERTUMBUHAN DAN HASIL CABAI MERAH (Capsicum annum L) PADA PEMBERIAN BERBAGAI PUPUK BIOORGANIK FOSFAT - Lia Natalia Tansile; Abdul Rauf; Syamsiar Syamsiar (Fakultas Pertanian, Universitas Tadulako, 2022)
Bioorganic phosphate fertilizers are becoming increasingly popular as a sustainable alternative to traditional chemical fertilizers. In the experimental field of the Faculty of Agriculture, UNTAD, research on the application of bioorganic phosphate fertilizer to chili (Capsicum annuum L.) was carried out. The objective was to establish the right dose of bioorganic phosphate fertilizers and how they would affect chili plant growth. The findings demonstrated that, with the exception of the number of branches, the use of bioorganic phosphate fertilizer significantly increased plant growth and agricultural yields. The relationship between the dose and the plant pattern's response is non-linier. The red chili plants responded better to the 2 g fertilizer plant-1 dose compared to the other treatments. The plants flowered earlier and produced the maximum amount (32.78 g) at this dose, an increase of 8 times above the control.